A poesia de Arriete Vilela: diálogos entre Mnemosine e Lete - Santos, Elaine Cristina Rapôso dos (2017)
This Doctoral Dissertation studies the poetry of the Brazilian writer Arriete Vilela, from the emergence of Eu, em versos e prosa (VILELA, 1971), her first book, until the publication of Obra poética reunida (VILELA, 2010). Turning to this corpus¸ this study analyses the relation between memory and forgetfulness to demonstrate that the costruction of the text is developed from the connection between memory, forgetfulness and imagination. These cathegories are essencial to understand the construction of the labyrinth that characterizes the studied poetry, and they are adressed, in this work, from the theoretical perspectives of Bergson (2006), Ricoeur (2007), Freud (1974), and Bachelard (2009). From the suppression of the present, and the attempt to return to the past, the women who live in Arriete’s poetry develop an effort that materializes as their desire for self-comprehension. Such an effort that departs from the action of memory, from the work of the imagination, and from the interference of forgetfulness, attempts to reconstruct, and give new meaning to the experiences; it also brings to the poetic scene a group of women who can be seen as representing beings of memory and forgetfulness. The Freudian psychoanalytic notion of repression (1974) is essential to understand the way forgetfulness works, in this context, since the poetic persona constantly explores the attempt of a return to the past. According to Bachelard (2009), however, such a return is not static, and cannot be apprehended in its totality. Some contents, especially those that may inflict pain, and are, in its majority, related to childhood and the love experienced, are not accessible to the conscious plane, due to repression. The impossibility of recovering such contents interposes gaps in the construction of the text, which are fulfilled by imagination. The solidarity between memory and imagination, as well as the working of the mechanism of repression, that relegates some experiences from the past to forgetfulness, are elements that compose the studied work, where memory constitutes itself from the paths marked by the gaps left by forgetfulness. The text, as a result of this relation, is composed by such gaps, and is written from a craft language work which reveals itself, in the text, from the use of a meta-language, one of the main features of Arriete Vilela’s poetry.